A study on problem faced by final year students and the role of peers in the problem solving process / Ilham Alia Mat Isa - Mat Isa, Ilham Alia (2011)
This research is conducted to identify problems faced by the part eight students in completing their undergraduate studies and ways that they employed in dealing with the problems faced. Undeniably, there are numerous ways in coping with problems, however, this study will specifically focused on peers involvement in assisting the individual in solving the difficulty faced as final year students. The respondents for this study are among part eight students in the faculty of education. Questionnaires consisting of two major parts, which are demographic data and list of statements on students' perception of problems faced and ways of dealing with the difficulty were distributed to 100 participants. The researcher managed to collect 95 completed questionnaires which were further analyze in order to gain the result for this research. The data gained was analyzed descriptively. From the research, common problems faced by the students are listed. It was also identified that peers play a large role in helping the individuals in dealing with their problems. The possible ways that were offered by the part eight students' peers in helping them to face their problems were recognized. Overall, majority of the respondents agreed that friends did help them in dealing with their problems. Hopefully, this research will be an eye-opener for the curriculum developer, lecturers, counselors and university administrator in constructing the syllabus and considering the burden and stumbling blocks faced by the students in coping with all the other requirements expected of them. All the listed parties should play active roles in supporting the final year undergraduates to complete their studies. May all the assistance given uplift students' achievement and produce excellent graduates that will contribute in shifting the university into a world class university.